MEKANISME PENGHAPUSAN MEREK ATAS PRAKARSA MENTERI (STUDI KASUS PERKARA MEREK GEPREK BENSU) - Yoel Sitorus (LPPM Universitas Ekasakti Padang, 2023)
Trademark protection serves as an identification mark for a product. Therefore, the existence of brands that are identical to one another certainly creates confusion for the public regarding these brands. This is what happened in the Geprek Bensu and I Am Geprek Bensu problems. Thus, it is necessary to study the mechanism for removing marks on the initiative of the Minister.